The cost-effectiveness of azithromycin in reducing exacerbations in uncontrolled asthma. Issue 2 (18th February 2021) - O'Neill, Ciaran; Gibson, Peter G.; Heaney, Liam G.; Upham, John W.; Yang, Ian A.; Reynolds, Paul N.; Hodge, Sandra; Jenkins, Christine R.; Peters, Matthew; Marks, Guy B.; James, Alan L.; Simpson, Jodie L.
Add-on azithromycin (AZM) results in a significant reduction in exacerbations among adults with persistent uncontrolled asthma. The aim of this study was to assess the cost-effectiveness of add-on AZM in terms of healthcare and societal costs. The AMAZES trial randomly assigned 420 participants to AZM or placebo. Healthcare use and asthma exacerbations were measured during the treatment period. Healthcare use included all prescribed medicine and healthcare contacts. Costs of antimicrobial resistance (AMR) were estimated based on overall consumption and published estimates of costs. The value of an avoided exacerbation was based on published references. Differences in cost between the two groups were related to differences in exacerbations in a series of net monetary benefit estimates. Societal costs included lost productivity, over the counter medicines, steroid induced morbidity and AMR costs. Add-on AZM resulted in a reduction in healthcare costs (mean (95% CI)) including nights in hospital (AUD 433.70 (AUD 48.59–818.81) or EUR 260.22 (EUR 29.15–491.29)), unplanned healthcare visits (AUD 20.25 (AUD 5.23–35.27) or EUR 12.15 (EUR 3.14–21.16)), antibiotic costs (AUD 14.88 (AUD 7.55–22.21) or EUR 8.93 (EUR 4.53–13.33)) and oral corticosteroid costs (AUD 4.73 (AUD 0.82–8.64) or EUR 2.84 (EUR 0.49–5.18)); all p<0.05. Overall healthcare and societal costs were lower (AUD 77.30 (EUR 46.38) and AUD 256.22 (EUR 153.73) respectively) albeit not statistically significant. The net monetary benefit of add-on AZM was estimated to be AUD 2072.30 (95% CI AUD 1348.55–2805.23) or (EUR 1243.38 (EUR 809.13–1683.14) assuming a willingness to pay per exacerbation avoided of AUD 2651 (EUR 1590.60). Irrespective of the sensitivity analysis applied, the net monetary benefit for total, moderate and severe exacerbations remained positive and significant. Add-on AZM therapy in poorly controlled asthma was a cost-effective therapy. Costs associated with AMR did not influence estimated cost-effectiveness. Add-on AZM in the treatment of poorly controlled persistent asthma is cost-effective. It is associated with a positive net monetary benefit when costs including those associated with antimicrobial resistance are considered. https://bit.ly/31aZ3fi